A Glucurono(arabino)xylan Synthase Complex from Wheat Contains Members of the GT43, GT47, and GT75 Families and Functions Cooperatively(1)([C])([W])([OA]) - Zeng, Wei (American Society of Plant Biologists, 2010)
Glucuronoarabinoxylans (GAXs) are the major hemicelluloses in grass cell walls, but the proteins that synthesize them have previously been uncharacterized. The biosynthesis of GAXs would require at least three glycosyltransferases (GTs): xylosyltransferase (XylT), arabinosyltransferase (AraT), and glucuronosyltransferase (GlcAT). A combination of proteomics and transcriptomics analyses revealed three wheat (Triticum aestivum) glycosyltransferase (TaGT) proteins from the GT43, GT47, and GT75 families as promising candidates involved in GAX synthesis in wheat, namely TaGT43-4, TaGT47-13, and TaGT75-4. Coimmunoprecipitation experiments using specific antibodies produced against TaGT43-4 allowed the immunopurification of a complex containing these three GT proteins. The affinity-purified complex also showed GAX-XylT, GAX-AraT, and GAX-GlcAT activities that work in a cooperative manner. UDP Xyl strongly enhanced both AraT and GlcAT activities. However, while UDP arabinopyranose stimulated the XylT activity, it had only limited effect on GlcAT activity. Similarly, UDP GlcUA stimulated the XylT activity but had only limited effect on AraT activity. The [(14)C]GAX polymer synthesized by the affinity-purified complex contained Xyl, Ara, and GlcUA in a ratio of 45:12:1, respectively. When this product was digested with purified endoxylanase III and analyzed by high-pH anion-exchange chromatography, only two oligosaccharides were obtained, suggesting a regular structure. One of the two oligosaccharides has six Xyls and two Aras, and the second oligosaccharide contains Xyl, Ara, and GlcUA in a ratio of 40:8:1, respectively. Our results provide a direct link of the involvement of TaGT43-4, TaGT47-13, and TaGT75-4 proteins (as a core complex) in the synthesis of GAX polymer in wheat.